Heritability and correlation coefficient analysis for yield and its components in rice (Oryza sativa L.) - Akinwale, M.G.; Gregorio, G.; Nwilene, F.; Akinyele, B.O.; Ogunbayo, S.A.; Odiyi, A.C. (Academic Journals, 2011)
The objectives of this study were to estimate the phenotypic and genotypic coefficients of variation, broad sense heritability, genetic gain and correlations in rice (Oryza sativa L.). The experiment was laid out in a randomized complete block design (RCBD) with three replications in the International Institute of Tropical Agriculture, Ibadan, Nigeria during 2008/2009 cropping season. Genotypes differed significantly at (p>0.001) for all the traits studied, which implies that the genotypes constitute a pool of germplasm with adequate genetic variability. Genotypic coefficients of variation were lower than the corresponding phenotypic coefficients in all the traits studied, indicating considerable influence of the environment on the expression of the traits. High to medium broad sense heritability estimates observed on days to heading, days to maturity, plant height, grain yield and number of grains per panicle, panicle weight, number of panicles per m2 and panicle length suggests high component of heritable portion of variation, which is the portion exploited by breeder and that selection for these traits can be achieved directly based on their phenotypic performance. The low broad sense heritability observed for the number of tillers per plant and 1000 grain weight is indicative of the influence of the environment on these traits. Low heritability of these traits indicates the ineffectiveness of direct selection for these traits. High to medium heritability and genetic advance were recorded for the number of grains per panicle, grain yield, panicle weight and the number of panicles per plant. This suggests that these traits are primarily under genetic control and selection for them can be achieved through their phenotypic performance. Grain yield exhibited significantly positive correlation with the number of tillers per plant (r = 0.58**), panicle weight (r =0.60*) and number of grains per panicle (r= 0.52*). Therefore, the results suggest that these traits can be used for grain yield selection.